Key process areas (KPAs), key processes, and key pratices of enablers in osh management systems - Misnan, Mohd. Saidin; Mohammed, Abdul Hakim; Chong, Shew Huey (2006)
This paper reports on finding of the study of the key process areas, key processes, and key practices of enablers in OSH. Key processes of the OSH management system were categorized under 4 major topic areas: OSH requirements management, OSH planning, hazard management, and OSH measurement and analysis. The enablers of the OSH evaluation can be divided into 4 parts: commitment to perform, ability to perform, activities performed, and verifying implementation. Each of them contains at least two key practices to indicate whether the implementation and institutionalization of the key processes is effective, repeatable and lasting.